ChemInform Abstract: Electrophilic Cyclization of o‐Anisole‐ and o‐Thioanisole‐Substituted Ynamides: Synthesis of 2‐Amidobenzofurans and 2‐Amidobenzothiophenes. Issue 42 (1st October 2013) - Kong, Yulong; Yu, Lian; Fu, Lingzi; Cao, Jian; Lai, Guoqiao; Cui, Yuming; Hu, Ziqiang; Wang, Guanhai
Abstract A simple protocol allows the electrophilic cyclization of the title ynamides with iodine, NBS, or NCS to provide benzofurane and benzothiophene derivatives.